On the Progression of COVID-19 in Portugal: A Comparative Analysis of Active Cases Using Non-linear Regression - Milhinhos, Ana; Costa, Pedro M. (Frontiers in Public Health, 2020)
Portugal was often portrayed as a relatively successful case in control of the COVID-19’s March 2020 outbreak in Europe due to timely confinement measures, commonly referred to as the ‘lockdown’. As in other European Union member states, by late April, Portugal was preparing the phased loosening of such measures, scheduled for the beginning of May. Despite a modest reduction in infection rates by that time, data was insufficient to reliably forecast imminent scenarios. Using South Korea data as scaffold, which became a paradigmatic case of recovery following a high number of infected people, we fitted Portuguese data to biphasic models using non-linear regression and compared between the two countries. The models, which yielded good fit, showed that recovery would be slow, with over 50% active cases months after lockdown. These findings acted at the time as a warning, showing that a high number of infected, together with an unknown number of asymptomatic carriers, could increase the risk of a slow recovery if not of new outbreaks. A month later, the models showed more favourable outcomes. However, shortly after, as the effects of leaving the lockdown became evident, the number of infections began rising again, leaving Portugal in a situation of inward and outward travel restrictions and baffling even the most conservative forecasts for the clearing of the pandemic.